The examination of the relationship between nursing students' depression, anxiety and stress levels and restrictive, emotional, and external eating behaviors in COVID‐19 social isolation process. Issue 2 (3rd December 2020) - Kalkan Uğurlu, Yasemin; Mataracı Değirmenci, Duygu; Durgun, Hanife; Gök Uğur, Hacer
Abstract: Purpose: This study was conducted to examine the relationship between students' anxiety, depression, stress levels, and emotional, external, restrictive eating behaviors in the coronavirus disease 2019 (COVID‐19) process. Design and Methods: This study was conducted in included university involving 411 nursing students who completed the Personal Information Form, Depression, Anxiety, Stress Scale, and the Dutch Eating Behavior Questionnaire. Kruskal–Wallis Test, Mann–Whitney U test, and Spearman's correlation test were used to evaluate the data. Findings: In the correlation between Depression, Anxiety, Stress Scale subscale scores, and the Dutch Eating Behavior Questionnaire subscale scores, there was no significant relationship between only depression and restrictive eating. Practice Implications: It was determined that the COVID‐19 pandemic process affected the mental health of nursing students and their eating behaviors.